Studies on Paliperidone in OROS Tablets: Extraction Procedure and Chromatographic Analysis. (4th March 2012) - Barbosa, Fábio; Mantovani, Luciano; Garcia, Cássia V.; Mendez, Andreas S. L.
Abstract : A stability-indicating liquid chromatographic (LC) method was studied for the determination of paliperidone in osmotic-controlled release oral delivery system (OROS) tablets. A tablet extraction procedure was developed by testing the efficiency of solvents (water, HCl, NaOH, acetonitrile, methanol) and techniques (ultrasonic bath, magnetic stirrer), and evaluating the release of the drug with respect to time. A forced degradation study was conducted to demonstrate the stability-indicating power of the method. Chromatographic separation was achieved using an isocratic elution in a reversed-phase system with a mobile phase prepared from a mixture of phosphate buffer and acetonitrile. The use of an ultrasonic bath demonstrated paliperidone release from OROS tablets in a total time of 60 min. Verifying the efficiency of the chromatographic procedure, the theoretical plates (N = 12634.21 ) and tailing factor (tf = 1.31 ) were constant during repeated injections. The retention time of paliperidone was 4.8 min, and the method was validated within the concentration range of 10–50 μg mL -1 (r = 0.9999 ). Adequate reproducibility (RSD% = 0.30–0.59), interday precision (RSD % = 1.81 ), and accuracy were obtained. The proposed method was successfully applied to paliperidone determination in the presence of degradation products, and an efficient extraction procedure from the OROS tablets was developed.